2022
DOI: 10.1155/2022/8370842
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Stereotactic Body Radiation Therapy Combined with Thermoplastic Fixation on Set-Up Errors in Breast Cancer Patients Undergoing Radiotherapy

Abstract: Objective. To investigate the effect of stereotactic radiotherapy (SBRT) combined with thermoplastic fixation on set-up error in breast cancer (BC) patients undergoing radiotherapy. Methods. Ninety BC patients undergoing radiotherapy who were treated in our hospital (May 2019-May 2020) were selected as the research objects and equally divided into the experimental group and control group according to the order of hospitalization, with 45 patients in each group. The control group received conventional radiother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%